(untitled) (Research, Society and Development, 2021)
Introduction: Hematopoietic Stem Cell Retransplantation is the only treatment option for those who have developed graft failure in previously transplanted stem cells or who relapsed. Objective: To analyze and develop the concept of Hematopoietic Stem Cell Retransplantation from Rodgers’ evolutionary perspective. Materials e methods: A documentary concept analysis study carried out from the six stages proposed by Rodgers. Data collection occurred by searching for articles in international databases. The studies were analyzed for the concept of Hematopoietic Stem Cell Retransplantation, its attributes, antecedents, consequents, substitute terms and related concepts. Results: “Second transplant” and the related concept “Secondary graft” stood out as a substitute term. The most frequent attributes, antecedents and consequences were respectively: only option/treatment form for graft rejection or failure; graft failure; and increased survival. Conclusion: As a result, the concept of retransplantation was developed. Hematopoietic Stem Cell Retransplantation includes other purposes in addition to the new transplant and brings together different types of cell sources.